2014
DOI: 10.1016/j.pt.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

What is the importance of zoonotic trichomonads for human health?

Abstract: Trichomonads are common parasites of many vertebrate and invertebrate species, with four species classically recognized as human parasites: Dientamoeba fragilis, Pentatrichomonas hominis, Trichomonas vaginalis, and Trichomonas tenax. The latter two species are considered human-specific; by contrast, D. fragilis and P. hominis have been isolated from domestic and farm mammals, demonstrating a wide host range and potential zoonotic origin. Several new studies have highlighted the zoonotic dimension of trichomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 79 publications
(145 reference statements)
6
105
0
8
Order By: Relevance
“…The parabasalian parasite is estimated to infect about 276 million new hosts annually worldwide [3], and in the US about 1 in 30 women tests positive for Trichomonas [4]. The parasite mainly affects the urogenital tract of both men and women, but it has also been isolated from the respiratory tract of infants [5] and adults [6] and a few in vitro studies have demonstrated that Trichomonas can attach to fibroblasts, muscle-and MDCK-cells [7,8]. Within the urogenital tract the parasite invades the squamous epithelium, which can not only lead to vaginitis/prostatitis, but also increase the risk of HIV transmission and the risk of low birth weights [9].…”
Section: Trichomonas Vaginalis At a Glancementioning
confidence: 99%
See 1 more Smart Citation
“…The parabasalian parasite is estimated to infect about 276 million new hosts annually worldwide [3], and in the US about 1 in 30 women tests positive for Trichomonas [4]. The parasite mainly affects the urogenital tract of both men and women, but it has also been isolated from the respiratory tract of infants [5] and adults [6] and a few in vitro studies have demonstrated that Trichomonas can attach to fibroblasts, muscle-and MDCK-cells [7,8]. Within the urogenital tract the parasite invades the squamous epithelium, which can not only lead to vaginitis/prostatitis, but also increase the risk of HIV transmission and the risk of low birth weights [9].…”
Section: Trichomonas Vaginalis At a Glancementioning
confidence: 99%
“…This suggest some sort of selection, but until more data on different strains becomes available, much of this largely remains speculative and comparing virulent factors (including exosomes) of bird and human Trichomonas spp. [6] might also help to shed some more light on the specificity of exosomes. In any case, if we predict that exosomes serve as a mean to communicate, then we need to expect them to differ depending on environmental conditions.…”
Section: Secretion Of Soluble Factorsmentioning
confidence: 99%
“…Biorąc pod uwagę fakt, że na świecie jest coraz więcej osób z obniżoną odpornością, można przypuszczać, że liczba inwazji wywoływanych przez te pierwotniaki będzie wzrastać. Tego typu inwazje mogą mieć zarówno charakter zoonoz, jak i antropozoonoz (70). Dowodzi tego przypadek wyizolowania T. canistomae od 72-letniego mężczyzny leczonego sterydami z powodu reumatoidalnego zapalenia stawów (36), a także zapalenie ślinianki wywołanej przez T. tenax u 13-letniej suki rasy jamnik, z zaawansowanym stadium periodontitis (88).…”
Section: Formy Współżyciaunclassified
“…T. vaginalis, który jest wyłącznie czynnikiem etiologicznym trichomonoz u ludzi -choroby układu moczowo-płciowego (70,80).…”
Section: Formy Współżyciaunclassified
“…Trichomoniasis abortion in human and animals occurs through infection with non-zoonotic Trichomonas spp., T. vaginalis and T. foetus, respectively, while the zoonotic species (T. fragilis, T. homonis, T. tenax and T. gallinae) are not causing abortion and responsible only for gastrointestinal disease (Maritz et al 2014). Similarly, babesiosis abortion occurs in animals through infection with non-zoonotic Babesia spp., B. bovis and B. equi, while the zoonotic species; B. divergens, B. canis and B. microti had not been incriminated in induction of abortion in both animals and man (Becker et al 2009).…”
Section: Introductionmentioning
confidence: 99%